Perfil do idoso assistido pela Estratégia de Saúde da Família no Município de Botucatu-SP - Camargo, Caio Cavassan de [UNESP]; Pintscher, Aryana Baptista [UNESP]; Arakaki, Selma Horie [UNESP]; Spiri, Wilza Carla [UNESP] (My University, 2012)
Considering the aging aspects: physiological changes, chronological, social behavior, healthy support, beyond of "Heath Eldery Policies", to give prominence to “Heath Family Strategy” created in 1994, we aimed to describe the experiences in the Health Family Units of Rubião Jr’s district and Jd. Iolanda’s neighborhood, Botucatu city, and analyze datas which express aspects of taking care of the elderly assisted. For this, it was done an investigation and protocol analyzes of described and amounted statistics data coming from them we create some graphics of elderly who lives at the studied catchment areas. There was a significant number of elderly in unities who showed similar proportion of man and woman and the total number of elderly, involved the attended area is bigger at Jd. Iolanda’s neighborhood. The data shows that despite elderly take significant part of treatments, there isn’t available form specific. To conclude, it is necessary a revaluation of values of health professionals and promoters to count on with better options to elderly take care.

Considerando os aspectos do envelhecimento: alterações fisiológicas, cronológicas, de comportamento social e sustentabilidade saudável, além da "Política de Saúde do Idoso", objetivamos relatar experiências nas Unidades de Saúde da Família do município de Botucatu, e analisar aspectos do cuidado ao idoso. Foram realizadas investigação e a descrição dos dados quantitativos. Observou-se número significativo de idosos nas unidades, em proporções similares de homens e mulheres. O total de idosos, em relação à área atendida, é maior no bairro Jardim Iolanda. Os dados demonstraram que, apesar dos idosos formarem parte significativa dos atendimentos, não há a disponibilidade de formulários específicos. Concluiu-se, então, ser necessário treinamento dos profissionais e promotores da saúde para oferecer melhores opções para o cuidado ao idoso.
The profile of the elderly assisted by the Family Health Strategy in Botucatu-SP
Keywords: Family health; Health policy; Aged; Saúde da família; Políticas de saúde; Idoso